2018
DOI: 10.21037/tau.2018.06.05
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging (MRI)-based radiomics for prostate cancer radiotherapy

Abstract: In radiotherapy (RT) of prostate cancer, dose escalation has been shown to reduce biochemical failure. Dose escalation only to determinate prostate tumor habitats has the potential to improve tumor control with less toxicity than when the entire prostate is dose escalated. Other issues in the treatment of the RT patient include the choice of the RT technique (hypo- or standard fractionation) and the use and length of concurrent/adjuvant androgen deprivation therapy (ADT). Up to 50% of high-risk men demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…In contrast, conventional MR imaging is commonly performed for patients with neurologic symptoms in clinical practice, and thus radiomics analysis of conventional MR imaging can be used more widely. Lastly, the MR images in our study were obtained using heterogeneous MR scanner types, with various acquisition parameters, which can affect radiomic features and quantitative analysis 39 , Nonetheless, the diagnostic performance of the radiomics model remained high in the validation cohort, which substantiates the good generalizability of the model.…”
Section: Limitationsmentioning
confidence: 65%
“…In contrast, conventional MR imaging is commonly performed for patients with neurologic symptoms in clinical practice, and thus radiomics analysis of conventional MR imaging can be used more widely. Lastly, the MR images in our study were obtained using heterogeneous MR scanner types, with various acquisition parameters, which can affect radiomic features and quantitative analysis 39 , Nonetheless, the diagnostic performance of the radiomics model remained high in the validation cohort, which substantiates the good generalizability of the model.…”
Section: Limitationsmentioning
confidence: 65%
“…Grey-level patterns from radiological images, used in radiomics, have been evaluated before [18] , [19] , [28] , and GLCM and Haralick [13] , [22] , [23] , [26] features are commonly used. Daniel et al [13] studied first order- and the GLCM- features before and after ADT.…”
Section: Discussionmentioning
confidence: 99%
“…For MRI, image texture analysis has been suggested as a supporting tool to separate tumour from normal tissue [15] , even in cases with low contrast between tumour and surrounding tissue [13] . Texture features for prostate cancer [16] , [17] , [18] , [19] can be derived using grey-level co-occurrence matrices (GLCM) with the aim to separate or classify different tissue types. To do so, different statistical features can be extracted from GLCM such as Haralick features [20] , thoroughly described and applied in several studies, both in its original form [13] , [21] , and in an invariant form independent of the number of grey-levels [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that radiomics has prospects in a broad array of applications, including early screening, accurate diagnosis, grading and staging, treatment and prognosis, and determination of molecular characteristics of brain tumors (42, 43). Radiomics has been shown to be important in predicting and assessing radiotherapeutic response in a variety of tumors, and its performance is significantly better than conventional methods (44), including lung cancer (45, 46), prostate cancer (47), rectal cancer (48). Therefore, we aimed to use a radiomics approach to predict the response of acromegaly to radiotherapy before treatment.…”
Section: Discussionmentioning
confidence: 99%